Surveying the Domesday Book - Fenwick, Helen (Medieval Settlement Research, 2023)
The data-rich Domesday Book has been explored in many ways, from the detail of each entry to its meaning and intention. In this new publication, Simon Keith, a retired Chartered Surveyor, aims to study the timeframe for the creation and compilation of the Domesday Book (DB) from the viewpoint of someone who has first-hand experience of valuing land. Keith sets out at the start how he views the DB as a ‘fiscal failure’, since he sees the purpose as fiscal in nature, particularly looking at arable land. Although he acknowledges there would be secondary value in the information recorded, taxation was its key focus. As it was never used directly to gather the taxation, he therefore deems DB a failure.